Comparative Efficacy of Three Minimally Invasive Procedures for Kümmell’s Disease: A Systematic Review and Network Meta-Analysis - Wang, Yajian; Liu, Bo; Sun, Zhenwei; Zhang, Yaning; Su, Jiangping (Frontiers in Surgery, 2022)
Background Percutaneous vertebroplasty (PVP), percutaneous kyphoplasty (PKP), and bone-filling mesh containers(BFC) are three viable minimally invasive techniques that have been used to treat Kümmell's disease(KD). However, there is still debate as to which is safer and more effective. This study summarized the pros and cons of the three techniques in the treatment of KD through network meta-analysis(NMA). Methods All eligible published clinical control studies comparing PVP, PKP, and BFC for KD up to December 2021 were collected by online search of Cochrane Library, PubMed, Embase, CNKI, Wanfang Database, and Chinese biomedical literature database. Data were extracted after screening, and Stata 16.0 software was used to perform the network meta-analysis. Results Four randomized controlled trials (RCTs) and 16 retrospective case-control studies (CCTs) with a total of 1114 patients were included. The NMA results showed no statistical difference between the 3 procedures in terms of improving patients' clinical symptoms. PKP was the most effective in correcting kyphosis, while BFC was the most effective in managing the occurrence of cement leakage. No statistical differences were found in the incidence of new vertebral fractures in adjacent segments. Conclusions Ranking analysis showed that BFC has the highest likelihood of being the optimal procedure for the treatment of KD, based on a combined assessment of effectiveness in improving patients’ symptoms and safety in the occurrence of adverse events.